The Footbonaut as a new football-specific skills test: reproducibility and age-related differences in highly trained youth players. Issue 3 (3rd July 2019) - Beavan, Adam; Fransen, Job; Spielmann, Jan; Mayer, Jan; Skorski, Sabrina; Meyer, Tim
ABSTRACT: Purpose: In sport, assessments are routinely administered to give an indication of performance. Assessing a skill requires external factors to dictate how and when the action is performed, highlighting the need for skill assessments to closely replicate the perception-action couplings experienced in football game play. Therefore, this study investigated if the Footbonaut is a valid and reliable football-specific skill assessment tool. Methods: Footbonaut performance scores from 152 male players from U12 to U23 representing a professional German Bundesliga club during the 2016/2017 season were analysed. Results: Pearson correlations ( r ) and coefficient of variation (CV) for the correct number of passes in a target (CV = 7.5–11.1; r = 0.48; p < 0.001), the speed at which they completed each trial (CV = 2.6–5.1; r = 0.70; p < 0.001), and a computer-generated point score (CV = 7.4–12.3; r = 0.77; p < 0.001) demonstrated acceptable test–retest reliability. Moreover, a MANOVA revealed a strong multivariate effect of age group on speed and accuracy combined ( F = 7.80, p < 0.001, ES = 0.28), demonstrating the Footbonaut's construct validity. Conclusion: The results in this study demonstrated that the Footbonaut is a valid and reliable assessment of football-specific skill.